2021
DOI: 10.1039/d0cp04992a
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the nature of citric acid:l-arginine:water mixtures: the bifunctional role of water

Abstract: DES? Solution? Either a DES or other type of non-ideal solution, the studied systems are non-ideal mixtures. Their liquefaction is mediated by water through the formation of charged species and cross interactions between the mixture constituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…NMR spectroscopy was performed for the identification of hydrogen-bonding interactions between the components of the LTTMs, the predominant type of interactions responsible for their formation. The NMR spectra of the C:A:W ( Figure S2 in Supplementary material ) were previously reported by the authors [ 29 ], where the results supported the presence of an altered hydrogen-bonding network in the ternary mixture. Regarding G:S and pure components, their H 1 NMR spectra were here analysed.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…NMR spectroscopy was performed for the identification of hydrogen-bonding interactions between the components of the LTTMs, the predominant type of interactions responsible for their formation. The NMR spectra of the C:A:W ( Figure S2 in Supplementary material ) were previously reported by the authors [ 29 ], where the results supported the presence of an altered hydrogen-bonding network in the ternary mixture. Regarding G:S and pure components, their H 1 NMR spectra were here analysed.…”
Section: Resultssupporting
confidence: 79%
“…DSC is often used in the characterization of LTTMs, as they are commonly defined as mixtures with low-temperature transitions, either glass transition temperatures (T g ) and/or melting temperatures (T m ). The DSC results for the C:A:W system were previously reported by us (see Figure S1 in supplementary material ) [ 29 ]. From those results, although a melting peak around −13 °C was detected for this system, it was attributed to the free water component of the mixture.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Thus, while the melting point depression is closely linked with the hydrogen bond (HB) network formed between the components, a comprehensive picture of the relationship between structure, molecular interactions, and the properties of the DES remains elusive. Furthermore, the presence of water, either as a component to form a DES or to tailor properties such as the viscosity, raised several questions about these solvents: is there a water ratio at which a transition from a binary to a ternary (where water is the third component) DES occurs? Is there a well-defined crossover between a DES and an aqueous solution?…”
Section: Introductionmentioning
confidence: 99%
“…However, adding more than 50% of water to the system could lead to a disruption of the hydrogen bonds and dilution of the components, creating a solution (Dai et al, 2015;Craveiro et al, 2016). In previous studies, the possibility of pH itself affect the solubility of other components in the mixture was explored and it was observed that the slight variation of pH did not affect the solubility of these eutectic mixtures and due to that, the pH was not considered in molecular dynamics (MD) studies (Santos et al, 2018;Roda et al, 2021).…”
Section: Introductionmentioning
confidence: 99%